The unique synergy between coordinatively unsaturated zirconium and atomically dispersed iron in tremella-like MOFs for bisphenol A removal - Huang, Zhikun; Yu, Haojie; Wang, Li; Liu, Xiaowei; Shen, Sudan; Ren, Shuning; Gong, Xiaodan; Huang, Yudi; Yang, Jian; Wu, Xudong; Ouyang, Chenguang (Journal of alloys and compounds, 2025)
Metal-organic frameworks (MOFs) have emerged as promising candidate materials for the photocatalytic degradation of toxic organic pollutants in wastewater. However, most MOFs exhibit poor stability in aqueous environments, limited accessible active sites, and insufficient absorption of visible light. Herein, we successfully synthesized a highly stable tremella-like MOF (TMOF), which features coordinatively unsaturated zirconium centers and abundant atomically dispersed iron sites. This TMOF demonstrated superior photocatalytic performance in activating peroxymonosulfate (PMS) for the degradation of bisphenol A (BPA) in aqueous solutions. In the TMOF/PMS/Vis system, BPA was completely removed within 60 minutes, with hydroxyl radicals (·OH) and sulfate radicals (SO4-·) serving as the primary reactive oxygen species (ROS). Furthermore, based on experimental results and DFT calculations, the coordinatively unsaturated Zr centers can not only effectively promote the adsorption of BPA, but also can accelerate the decomposition of PMS to generate adequate ROS, thereby enhancing the photocatalytic activity of TMOF. Additionally, the long-term usability of TMOF, the BPA degradation pathway, and the toxicities of the generated intermediates have been systematically demonstrated. This study aims to provide a stable MOF with high catalytic activity in aqueous environments to efficiently remove recalcitrant and toxic pollutants from water. •The unsaturated Zr sites and single Fe sites are introduced in TMOF.•The enhanced photocatalytic activity is derived from Zr-CUS and single Fe site.•The interfacial interactions between TMOF and BPA/PMS were examined.